A feasible random copolymer approach for high-efficiency polymeric photovoltaic cells. Issue 29 (8th July 2016) - Lee, You-Sun; Lee, Ji Young; Bang, Su-Mi; Lim, Bogyu; Lee, Jaechol; Na, Seok-In
Abstract : Conjugated random copolymers with non-covalent intramolecular interaction are synthesized and used as electron-donor materials for highly efficient organic solar cells. Abstract : Two random copolymers based on (2, 5-difluorophenylene)dithiophene and dialkoxybenzothiadiazole with benzodithiophene (P1 ) or thiophene (P2 ) as the third conjugated bridge having sulfur and fluorine (S⋯F) and/or oxygen (S⋯O) non-covalent intramolecular interaction are synthesized and characterized. In spite of a molecular weight difference over three times between both polymers, P1 andP2 possess similar solubility in organic solvents and thermal stability ( T d ∼ 320 °C), which means probably due to thatP1 with bulky alkylthiophene substituted benzodithiophene as a third conjugated bridge has less non-covalent intramolecular interaction than that ofP2 with thiophene as a bridge. Both polymers were used as electron donors in bulk heterojunction organic photovoltaics (BHJ OPV) with PC71 BM as an acceptor. From the photovoltaic measurements it was revealed thatP2 shows higher power conversion efficiency (PCE) of up to 6.82% than that ofP1 (2.44%). After 1, 8-diiodooctane (DIO) treatments as a processing additive, theP1 andP2 devices show a significantly improved PCE of 5.95% forP1 and 7.71% forP2 . The surface morphology analysis of the blend films using the atomic force microscope (AFM) reveals that theP1 : PC71 BM film shows macrophase separation, while theP2 film has a smooth morphology. After DIO treatments, the morphology of both polymer blend films is improved with better bi-continuous nanoscale networks. Charge carrier mobilities through the space charge limited current (SCLC) method demonstrate thatP2 with the thiophene bridge has higher charge carrier mobilities thanP1 . In particular, an inverted structured BHJ OPV withP2 exhibits a PCE of 8.50%, which is the highest PCE reported in the literature regarding random copolymers.